Using Mathematical Modeling Estimest of Alteration Trend of Small Mammals (Rodentia) in Dongphouvieng National Protected Area, (Case Study Dongsaki) Phin District Savannakhet Province - Phonesay , Latsamy; Sootkongthong, Koonphet; Sonedavong, Phouvanh; Syharath, Sysavath (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research aims to assess trends in changes in small mammal populations (Rodentia) in the Dong Phouvieng National Protected Area using mathematical modeling. The case study focuses on the Dongsaki Protected Area in Phin District. The target group for this study was small mammals (Rodentia). Data were collected through field surveys conducted along study routes located primarily in deep forests, mixed deciduous forests, and open forests. Additional data were gathered through interviews with local residents, forest conservation officials, and community members familiar with wildlife in the area. The data, spanning the years 1990 to 2024, were analyzed using mathematical models to identify trends in mammal populations. The results indicate a general decline in the populations of small mammals. Notably, the Northern Treeshrew (Tupaia belangeri) showed the most significant decrease, with an average population decline of 9.25% every five years. In comparison, squirrels (Sciuridae spp.), chipmunks (Sciuridae spp.), and the Noisy Rat (Leopoldamys sabanus) exhibited smaller declines of 5.43%, 5.23%, and 5.21% respectively every five years. Findings from focus group interviews suggest that the decline in small mammal populations is primarily due to natural disasters, habitat encroachment, and hunting for subsistence and trade. These pressures have contributed to environmental degradation, ecosystem changes, drying water sources, and the migration of some species to other areas. As a result, mammal populations in the region continue to decline annually. Therefore, effective management of wildlife habitats is essential to prevent further encroachment and wildfires whether natural or human-induced in order to conserve biodiversity and protect wildlife for the future.